Interconnectedness of the banking sector as a vulnerability to crises. (28th October 2018) - Peltonen, Tuomas Antero; Rancan, Michela; Sarlin, Peter
Abstract: This paper uses macro‐network to measure the interconnectedness of the banking sector and relates it to banking crises in Europe. Beyond cross‐border financial linkages of the banking sector, the macronetwork also accounts for financial linkages to the other main financial and nonfinancial sectors within the economy. We find that a more central position of the banking sector in the macronetwork significantly increases the probability of a banking crisis. By analysing the different types of risk exposures, our evidence shows that credit is an important source of vulnerability. Finally, our early‐warning models augmented with interconnectedness measures outperform traditional models in terms of out‐of‐sample predictions.